PENGENALAN INOVASI TEKNOLOGI: KUNJUNGAN INDUSTRI SMKS YABHINKA KE PT CHARGED INDONESIA - Sembiring, Evi Dora; Pertiwi, Sari Putri; Anggriawan, Muhammad Angga; Samsinar, Ade; Handayani, Novi (Batara Wisnu : Indonesian Journal of Community Services, 2024)
Technological innovation is currently developing rapidly and has been applied in various industrial sectors, providing sophistication and benefits in its use. PT Charged Indonesia is a company that operates in the field of renewable energy technology, namely assembling electric motors that use smart systems, portable batteries, and are easy to use. Industrial visits are one of the important activities in the world of vocational education which aims to introduce students to real work environments, especially industries in the field of technological innovation.  This article discusses the industrial visit carried out by the YABHINKA SMKS team to PT Charged Indonesia with the aim of directly introducing technological innovations in the industrial sector in the field of motor assembly. The implementation method is divided into 3 (three) stages, namely the introduction stage, assembly stage and feasibility test stage. This activity provides a better understanding of the assembly process, technological innovation, industry needs for skilled labor and has a positive impact and benefits on the world of vocational education. Based on the results of implementing this activity, students gain experience regarding the introduction of technological innovation in the real world which opens up insight into the importance of education that is relevant to the needs of industry in the future